Copper-Catalyzed Aerobic C–H Trifluoromethylation of Phenanthrolines - Zhu, Cheng-Liang; Zhang, Yong-Qiang; Yuan, Yong-An; Xu, Hao (Synlett, 2015)
Direct C–H trifluoromethylation of heterocycles is a valuable transformation. In particular, nonprecious metal-catalyzed C–H trifluoromethylation processes, which do not proceed through CF3 radical species, have been less developed. In this cluster report, a new copper-catalyzed aerobic C–H trifluoromethylation of phenanthrolines is described. This transformation affords trifluoromethylated phenanthrolines that have not been synthesized and preliminary mechanistic studies suggest that the CF3 group transfer may occur through cooperative activation.
Keywords: copper; fluorine; oxygen; oxidation; heterocycles